Diversity of Zingiberaceae Family in Pu Mat National Park, Nghe An Province - Huong, Le Thi; Huong, Trinh Thi; Thin, Dau Ba; Chau, Dao Thi Minh; Thoan, Dao Thi (VNU Journal of Science: Natural Sciences and Technology, 2018)
This paper presents some results of research on family Zingiberaceae in Pu Mat National Park, Nghe An province, from 2015 to 2017. Total 48 species belonging to 11 genus of Zingiberaceae were collected and identified. There were 4 genera and 27 species found as new recorded for the plant list of Pu Mat published in 2017. Alpinia was the richest genus (17 species), then followed by Amomum (9 species), Zingiber (8 species), and other genera (1 to 4 species). The Zingiberaceae species live mainly in under the forest canopy, secondary forests, along streams, scrub and primary forest. The number of useful plant species of the Zingiberaceae is categorized as follows: 48 species supply essential oil, 32 species as medicinal plants, 7 species for spice, 5 species for edible and 2 species for ornamental. The Zingiberaceae in Pu Mat National park are mainly comprised of the tropical element (45.83%), endemic element (47.92%) and temperate element (2.08%). Keywords Biodiversity, National Park, Nghe An, Pu Mat, Zingiberaceae References 1. Nguyễn Quốc Bình, Nghiên cứu phân loại họ Gừng (Zingiberaceae) ở Việt Nam, Luận án Tiến sĩ Sinh học, Hà Nội, 2011. 2. Võ Văn Chi, Từ điển cây thuốcViệt Nam, Tập 1-2, NXB Y học, Hà Nội, 2012. 3. Phạm Hồng Ban, Nghiên cứu tính đa dạng sinh học của các hệ sinh thái sau nương rẫy ở vùng Tây Nam, Nghệ An, Luận án Tiến sĩ Sinh học, Vinh, 2000. 4. Nguyễn Anh Dũng, Nghiên cứu đa dạng hệ thực vật bậc cao có mạch ở xã Môn Sơn vùng đệm Vườn Quốc gia Pù Mát, Luận văn Thạc sĩ Sinh học, Vinh, 2002. 5. Nguyễn Nghĩa Thìn, Nguyễn Thanh Nhàn, Đa dạng thực vật Vườn Quốc gia Pù Mát, NXB Nông nghiệp, Hà Nội, 2004. 6. Đỗ Ngọc Đài, Nguyễn Thanh Nhàn, Phạm Hồng Ban, Lý Ngọc Sâm, Etlingera yunnanensis (T. L. Wu & S. J. Chen) R. M. Sm. (Zingiberaceae) loài bổ sung cho hệ thực vật Việt Nam, Tạp chí Khoa học, Đại học Quốc gia Hà Nội, 31(4S) (2015), 35-38 7. Lê Thị Hương, Trần Thế Bách, Nguyễn Quốc Bình, Lý Ngọc Sâm, Bổ sung loài Riềng nhiều hoa (Alpinia polyantha D. Fang) cho hệ thực vật Việt Nam, Tạp chí Khoa học, Đại học Quốc gia Hà Nội, 31(4S) (2015) 35-38. 8. Lê Thị Hương, Nghiên cứu một số đặc điểm sinh học và thành phần hóa học tinh dầu của một số loài trong chi Riềng (Alpinia) và Sa nhân (Amomum) ở khu vực Bắc Trung Bộ, Luận án Tiến sĩ Sinh học, Hà Nội, 2016. 9. Đào Thị Minh Châu, Nghiên cứu lâm sản ngoài gỗ ở khu vực Vườn Quốc gia Pù Mát nhằm đề xuất các giải pháp khai thác và phát triển, Luận án Tiến sĩ Sinh học, Hà Nội, 2016. 10. Nguyễn Viết Hùng, Đỗ Ngọc Đài, Lê Thị Hương, Lý Ngọc Sâm, Nguyễn Trung Thành, Bổ sung loài Gừng sáng bóng (Zingiber nitens M. F. Newman) (Zingiberaceae) cho hệ thực vật Việt Nam, Tạp chí Khoa học Đại học Quốc gia Hà Nội, 33(2) (2017) 46-50. 11. Nguyễn Viết Hùng, Nghiên cứu thành phần hóa học tinh dầu của các loài thực vật ở VQG Pù Mát và đề xuất các giải pháp bảo tồn, Luận án Tiến sĩ Sinh học, Vinh, 2017. 12. Nguyễn Thanh Nhàn, Nghiên cứu đa dạng thực vật VQG Pù Mát và đề xuất các gaiir pháp bảo tồn, Luận án Tiến sĩ Sinh học, Vinh, 2017. 13. Nguyễn Nghĩa Thìn, Các phương pháp nghiên cứu thực vật, NXB Đại học Quốc gia Hà Nội, 2007. 14. Phạm Hoàng Hộ, Cây cỏ Việt Nam, Quyển 3, NXB trẻ, TP HCM, 2000. 15. Delin Wu & Kai Larsen, Zingiberaceae in Flora of China, Science Press, Beijing, and Missouri Botanical Garden Press, St. Louis, 2004. 16. Trần Đình Lý, 1900 loài cây có ích ở Việt Nam, NXB Thế giới, 1993. 17. Đỗ Tất Lợi, Những cây thuốc và vị thuốc Việt Nam, NXB Khoa học và Kỹ thuật, Hà Nội, 1999.